STEM–LITERACY INTEGRATION: MEMBANGUN PEMAHAMAN NARATIF DAN MATEMATIS MELALUI PLATFORM PEMBELAJARAN DIGITAL - Nensy Megawati Simanjuntak; Sulis Janu Hartati; Sumartono Sumartono; Herlina Simangunsong; Dedi Setyawan; Arumtyas Puspitaning Padmasari (Aksara, 2025)
The integration of literacy and numeracy has become a crucial priority in modern education in response to the increasing role of digital technology in learning. The need for an approach that connects narrative comprehension with mathematical reasoning has driven the development of the STEM– Literacy Integration model. This study aims to analyze the effectiveness of the model, which is characterized by the use of contextual mathematical narratives, cross-disciplinary problem solving, multimodal digital representations, and adaptive learning pathways that link language comprehension with numerical reasoning. The model was implemented through a digital learning platform to strengthen students’ reading comprehension and numeracy skills. The study employed a mixed methods approach with a quasi-experimental design involving 120 junior high school students in Surabaya, who were divided into experimental and control groups. Quantitative data were obtained through narrative literacy tests and numeracy assessments, while qualitative data were collected through interviews, observations of digital learning activities, and learning analytics. The results showed a significant improvement in reading comprehension and numeracy performance in the experimental group (p < 0.05). Thematic analysis revealed that the integration of mathematical storytelling, interactive simulations, visual–verbal reinforcement, and real-world STEM contexts strengthened the cognitive connection between language and mathematical concepts. This study concludes that the STEM– Literacy Integration model is effective in simultaneously enhancing literacy and numeracy in the digital era.